PENGARUH KERAGAMAN PRODUK, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA BABOKK BOUTIQUE DI KABUPATEN SUMBAWA - Sya’rani, Saofi Awalia; Hartini (Jurnal Nusa Manajemen, 2024)
Babokk boutique is one of the boutiques in Sumbawa Regency. Babokk boutique is located in the Karang Goreng neighborhood, Brang Bara Village, Sumbawa District, Sumbawa Regency. This research aims to examine the influence of product diversity, service quality and location on purchasing decisions at Babokk Boutique in Sumbawa Regency. In this study the author used aquantitative method with an associative type with data collection techniques through distributing questionnaires. The population in this study were people in the Sumbawa Regency area, people who had visited Babokk Boutique at least once. The sample in the research involved 100 respondents. The data obtained in this research is in the form of numerical data which is then processed using software such as SPSS version 26. The results of this research show that product diversity and location have a positive and significant effect on purchasing decisions at Babokk Boutique in Sumbawa Regency and service quality do not partially influence purchasing decisions at Babokk Boutique in Sumbawa Regency.